Current scenario of COVID-19 pandemics in the top ten worst-affected countries based on total cases, recovery, and death cases - Regmi, Sagar; Malla, Komal Prasad; Adhikari, Rameshwar (Applied Science and Technology Annals, 2020)
Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and first detected in Wuhan, Hubei Province, China in December 2019 and spread across China and abroad. On 11th March 2020, WHO officially declared pandemic on for COVID-19. This review presents transmission mode of the COVID-19 in terms of case, death, and analysis of active cases in top ten worst affected countries. The data presented in the paper is taken from Worldometer which collects its statistical data from various reliable sources including United Nations (UN), World Health Organization (WHO) and others. Furthermore, the review presents the data analysis of recovery cases in the top 10 worst affected countries as of 24th May 2020. Such simple analysis of recovery case from COVID-19 will be helpful for the government to make its plan and policy.